A multi-level assessment of shared decision making: An evaluation of clinician and patient attitudes and behaviors and the identification of predictive profiles - Steven Haimowitz; Karyn Ruiz-Cordell; Katherine Joubin; Regina Sih-Meynier (Cogent Medicine, 2020)
Abstract   The objective of this study was to gain a greater understanding of shared decision making (SDM) by identifying the behaviors and attitudes of healthcare professionals (HCP) and patients that are associated with varying levels of SDM performance. The study centered on HCP and patient surveys that assessed a participant’s degree of endorsement of SDM favorable behaviors by asking them to predict how they might address a specific decision point in various healthcare interactions. Using quantitative (descriptive analytics, predictive and mixture modeling) and qualitative methods (grounded theory) to analyze the data, SDM skills were quantified in HCP and patient populations, and demographic and attitudinal factors that facilitate or hinder successful implementation of SDM were identified. Distinct HCP profiles (Motivated but Cautious, Insufficiently Engaged, and Pro-Autonomous) and patient profiles (Pro-Paternalistic, Pro-Autonomous, and Unconcerned but Open-Minded) were then defined. By characterizing these distinct profiles and the attitudes and preferences that are associated with one another, these results can be directly utilized by educational providers interested in teaching SDM skills to enable HCPs to individualize their SDM approach based on the recognition of these profiles while also providing the self-assessment needed to modify their own behaviors.